Climate change skepticism and index versus standard crop insurance demand in coastal Bangladesh - Akter, Sonia (Reg Environ Change, 2017)
This paper investigates if climate change skepticism, farmers’ fatalistic beliefs, and insurance plan design influence interest in crop weather insurance. While studies of the influence of fatalism on disaster preparedness are common, the ways in which fatalism influences climate change skepticism, and in turn affects farmers’ interest in crop insurance, have not been previously investigated. An additional objective was to understand farmers’ preferences for index versus standard insurance options, the former entailing damage compensation based on post-hazard assessment, the latter tying damage compensation to a set of weather parameter thresholds. A discrete choice experiment was conducted with maize farmers on a climate-risk prone island in coastal Bangladesh. Most farmers were insurance averse. Those who chose insurance were however significantly more likely to select standard as opposed to index-based insurance. Insurance demand was significantly and positively correlated with farmers’ concern about the adverse livelihood impacts of climate change. Farmers who exhibited fatalistic views regarding the consequences of climate change were significantly less likely to opt for insurance of either kind. These findings imply that the prospect for farmers’ investment in insurance is conditioned by their understanding of climate change risks and the utility of adaptation, in addition to insurance scheme design.